2004
DOI: 10.1021/np0400609
|View full text |Cite
|
Sign up to set email alerts
|

Dibenzyl Bromophenols with Diverse Dimerization Patterns from the Brown Alga Leathesia nana

Abstract: Six novel dibenzyl bromophenols (1-6) with different dimerization patterns and two propyl bromophenol derivatives (7 and 8), together with 11 known bromophenol derivatives, were isolated from the ethanolic extract of the brown alga Leathesia nana. On the basis of spectroscopic methods the structures of the new compounds were determined as 5,6'-diethyloxymethyl-3,4,2'-tribromo-2,3',4'-trihydroxydiphenyl ether (1), 2-(2,3-dibromo-4,5-dihydroxybenzyl)-3,5-dihydroxy-4-methoxybenzyl alcohol (2), 6-(2,3-dibromo-4,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 24 publications
0
67
0
Order By: Relevance
“…Halis Türker Balaydın 1,2 , Hakan Soyut 1,3 , Deniz Ekinci 4 , Süleyman Göksu 1 , Şükrü Beydemir localization, catalytic activity and susceptibility to different classes of inhibitors. Some of these isozymes are cytosolic (CA I, CA II, CA III, CA VII and CA XIII), others are membrane-bound (CA IV, CA IX, CA XII and CA XIV), two are mitochondrial (CA VA and CA VB), and one is secreted in saliva (CA VI).…”
Section: Synthesis and Carbonic Anhydrase Inhibitory Properties Of Nomentioning
confidence: 99%
See 2 more Smart Citations
“…Halis Türker Balaydın 1,2 , Hakan Soyut 1,3 , Deniz Ekinci 4 , Süleyman Göksu 1 , Şükrü Beydemir localization, catalytic activity and susceptibility to different classes of inhibitors. Some of these isozymes are cytosolic (CA I, CA II, CA III, CA VII and CA XIII), others are membrane-bound (CA IV, CA IX, CA XII and CA XIV), two are mitochondrial (CA VA and CA VB), and one is secreted in saliva (CA VI).…”
Section: Synthesis and Carbonic Anhydrase Inhibitory Properties Of Nomentioning
confidence: 99%
“…The organic phase was separated and the water phase was extracted with EtOAc (2 × 30 mL). The combined organic phases were dried over Na 2 SO 4 …”
Section: Standard Procedures For Demethylation Of Compounds With Ome Bmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds have attracted much attention in the field of functional food and pharmaceutical agents 2 . It has been reported that naturally occurring bromophenol 1 shows enzyme inhibition 3 , cytotoxicity 4 , feeding deterrent 5 , anti-microbial 6 , anti-cancer 7 and anti-oxidant 8 activities. Aldose reductase 9 and carbonic anhydrase 10 inhibitory properties of natural products 2-3 have also been noted ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] We have continuously investigated the iron [14][15][16][17][18][19][20] -or gold [21][22][23] -catalyzed activation at the benzylic position of various skeletons accompanied by the benzylic C-O bond cleavage. During these investigations, the benzylic position of phthalan (1; n=1) as a benzene fused cyclic ether was found to be directly azidated in the presence of a gold catalyst and trimethylsilylazide (TMSN 3 ) without the C-O bond cleavage to give the 1-azido phthalan (2) (Chart 1). The direct azidations at the benzylic position of phthalan and isochroman (1; n=2) were previously accomplished using stoichiometric iodine reagents [9][10][11] in the presence of azido sources, such as TMSN 3 and NaN 3 .…”
Section: Gold-catalyzed Benzylicmentioning
confidence: 99%